Effect Of La2O3 Addition On The Hardness And Indentation Fracture Resistance Of Zta-Ceo2-La2o3 Ceramics - Rosli, Abdul Fatah Zulkarnain (Universiti Sains Malaysia, 2018)
The effect of La2O3 addition to zirconia toughened alumina (ZTA) ceramics has been studied. CeO2 has been added in the ZTA system which acts as sintering additive. ZTA-CeO2 composition mixed with La2O3 weight percentage from 0.1 wt.% by weight to 10 wt.% . The compositions for each type of composition have been mixed, dried for 24 hours in the oven at 100 °C. This mixture is then compressed using hydraulic compressor in the mold cylinder at 10 MPa to form sample pellets. Next, this ZTA sample is sintered at 1600 °C with 4 hours soaking in a pressureless sintering furnace. Each of the sample was tested with a Vickers indentation of 30 kgf equivalent to 294 N. The Vickers indentation is intended to measure the hardness of the Vickers value and indentation fracture resistance for each sample. From the optimisation, ceramic sample ZTA-CeO2 with 0.85 wt.% La2O3 addition showed the highest Vickers hardness result with 1760.28 HV. ZTA ceramic samples with 1 wt.% addition of La2O3 showed the highest indentation fracture resistance results with 8.28 KIFR. Based on the SEM results, microstructure showed that the amount of the grain is increase with the increase of weight percentage of La2O3 addition in the ZTA system. The presence of the secondary phase of the elongated rod-like grains formed was known as LaAl11O18. This secondary phase plays an important role in increasing the value of hardness.